Three-Dimensional Microstructure and Structural Representative Volume Element of the Intact and Remolded Loess - Lina Ma; Linxin Zhang; Xiaokun Hou; Songfeng Guo; Shengwen Qi (Applied Sciences)
On the Loess Plateau of China, the number of projects involving the excavation of mountains and the filling of valleys to create new land is rising. The loess excavated from the mountain is directly used as building material. After being filled into the valley and remolded, it serves as the foundation for overlying structures. However, significant differences in mechanical behavior exist between intact and remolded loess, leading to various issues such as differential settlement. Understanding the microstructure of loess is essential for improving our comprehension of its macro-level hydrological and mechanical behavior. Due to the inherent limitation of the conventional methods (e.g., scanning electron microscopy and mercury intrusion porosimetry) for microstructure investigation, an in-depth understanding of the three-dimensional (3D) microstructural differences between intact and remolded loess remains elusive. To address this gap, this study employs advanced X-ray micro-computed tomography (micro-CT) to investigate the 3D microstructure of both intact and remolded loess from two typical man-made new land creation projects. The three-dimensional microstructures are segmented into a series of cubes of varying dimensions to identify the structure’s representative volume element (RVE) and assess the uniformity of both loess types. The pore network of the RVE is quantitatively analyzed to characterize the microstructure. The results reveal significant disparities between the microstructure of intact and remolded loess, particularly in terms of uniformity, pore size distribution, and pore connectivity. Remolded loess exhibits a denser structure with poorer pore connectivity and greater heterogeneity compared to intact loess. These microstructural differences are attributed to the distinct formation processes of the two types of loess.